2003
DOI: 10.1074/jbc.m212996200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cyclization of a Potent Bowman-Birk Protease Inhibitor, Sunflower Trypsin Inhibitor-1, and Solution Structure of an Acyclic Precursor Peptide

Abstract: The most potent known naturally occurring BowmanBirk inhibitor, sunflower trypsin inhibitor-1 (SFTI-1), is a bicyclic 14-amino acid peptide from sunflower seeds comprising one disulfide bond and a cyclic backbone. At present, little is known about the cyclization mechanism of SFTI-1. We show here that an acyclic permutant of SFTI-1 open at its scissile bond, SFTI-1[6,5], also functions as an inhibitor of trypsin and that it can be enzymatically backbone-cyclized by incubation with bovine ␤-trypsin. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 39 publications
6
103
0
3
Order By: Relevance
“…The crystal structure of the free MASP-2 enzyme (40) showed that in the absence of bound substrate or inhibitor, the substrate binding groove on the enzyme is largely obstructed by long surface loops. Lacking structural information about the positions of these loops in a complex, we decided to design the library based on the smallest known natural trypsin inhibitor scaffold of the SFTI (27)(28)(29)(30).…”
Section: Design and Construction Of The Inhibitory Peptide-phage Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of the free MASP-2 enzyme (40) showed that in the absence of bound substrate or inhibitor, the substrate binding groove on the enzyme is largely obstructed by long surface loops. Lacking structural information about the positions of these loops in a complex, we decided to design the library based on the smallest known natural trypsin inhibitor scaffold of the SFTI (27)(28)(29)(30).…”
Section: Design and Construction Of The Inhibitory Peptide-phage Librarymentioning
confidence: 99%
“…Our target proteases were the MASP-1 and MASP-2, the initiator proteases of the lectin pathway. As a starting point for inhibitor selection, we used the sunflower trypsin inhibitor (SFTI), which has the shortest scaffold (only 14 aa) among the known natural SP inhibitors (27)(28)(29)(30). The selected peptides inhibit exclusively the lectin pathway among the three activation pathways of complement.…”
mentioning
confidence: 99%
“…These include the use of protein splicing catalyzed by inteins (16) or proteases (41,42) as well as thioester-based ligation using either modified inteins (27,29,30) or genetic code reprogramming (46). The ability to produce circular polypeptides using the tools of molecular biology has multiple biotechnological applications (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…MCoTI cyclotides and SFTI-1 are potent trypsin inhibitors, with K i values in the picomolar and nanomolar range, respectively. In both cases, the proteolytic enzyme trypsin was able to resynthesize the peptide bond between the P1 and P1Ј residues to form the native circular polypeptides (41,42). Although this approach has not yet been tested in vivo, there is mounting evidence that protease-catalyzed protein splicing is used in the biosynthesis of these naturally occurring circular polypeptides in plants.…”
Section: Backbone Cyclization Using Protease-catalyzed Transpeptidationmentioning
confidence: 99%
“…Ингибиторная петля, Thr4-Ile10, содержит сайт возможного расщепления трипсином Lys5-Ser6. Однако бoльшая часть молекул ингибитора остаётся негидролизованной: отношение количества нативного ингибитора к количеству гидролизованного ингибитора составляет 9:1 [65]. Вторичная петля, пентапептидный фрагмент, не участвует прямо во взаимодействии с протеазой, но стабилизирует структуру всего пептида за счёт формирования водородных связей с остатками ингибиторной петли.…”
Section: структуры кноттинов и ингибитора из семян подсолнечникаunclassified